1995
DOI: 10.1083/jcb.131.5.1205
|View full text |Cite
|
Sign up to set email alerts
|

Dictyostelium myosin I double mutants exhibit conditional defects in pinocytosis.

Abstract: Abstract. The functional relationship between three Dictyostelium myosin Is, myoA, myoB, and myoC, has been examined through the creation of double mutants.Two double mutants, myoA-/B-and myoB-/C-, exhibit similar conditional defects in fluid-phase pinocytosis. Double mutants grown in suspension culture are significantly impaired in their ability to take in nutrients from the medium, whereas they are almost indistinguishable from wild-type and single mutant strains when grown on a surface. The double mutants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
171
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 60 publications
(101 reference statements)
10
171
0
Order By: Relevance
“…Myosins of the class I have been localised to membrane ruffles and phagocytic cups in D. discoideum (Fukui et al 1989;Morita et al 1996), Entamoeba histolytica (Voigt et al 1999), Acanthamoeba castellanii (Baines et al 1992;Baines et al 1995;Jontes et al 1998) and macrophages (Allen and Aderem 1995;Swanson et al 1999). D. discoideum cells lacking either myosin IB, IC or IK exhibit significant reduction of the initial rate of particle uptake [Jung et al 1996; Schwarz EC, Neuhaus EM, Kistler C, and Soldati T: Dictyostelium MyoK, a novel type of myosin with crucial functions in motility and maintenance of cortical integrity (submitted)], and double deletion mutants (myoA-/myoB-, myoC-/myoB-) show conditional defects in fluid-phase pinocytosis (Jung et al 1996;Novak et al 1995).…”
Section: Molecular Aspects Of the Internalisation Processesmentioning
confidence: 99%
“…Myosins of the class I have been localised to membrane ruffles and phagocytic cups in D. discoideum (Fukui et al 1989;Morita et al 1996), Entamoeba histolytica (Voigt et al 1999), Acanthamoeba castellanii (Baines et al 1992;Baines et al 1995;Jontes et al 1998) and macrophages (Allen and Aderem 1995;Swanson et al 1999). D. discoideum cells lacking either myosin IB, IC or IK exhibit significant reduction of the initial rate of particle uptake [Jung et al 1996; Schwarz EC, Neuhaus EM, Kistler C, and Soldati T: Dictyostelium MyoK, a novel type of myosin with crucial functions in motility and maintenance of cortical integrity (submitted)], and double deletion mutants (myoA-/myoB-, myoC-/myoB-) show conditional defects in fluid-phase pinocytosis (Jung et al 1996;Novak et al 1995).…”
Section: Molecular Aspects Of the Internalisation Processesmentioning
confidence: 99%
“…Myosin-1 is able to cross-link the plasma membrane to the underlying actin cytoskeleton and plays a direct role in the control of cortical and membrane tension (11,12). These motor proteins can also drive vesicle trafficking, pseudopod retraction, and the uptake of particles and fluids by phagocytosis and micropinocytosis (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…This domain has been shown to serve as an ATP-independent secondary actin-binding site (56,57). In good agreement with the presence of both membrane-and actin-binding sites, myoB, myoC, and myoD have been localized at the cortex of vegetative cells and at the leading edge of motile D. discoideum cells during chemotaxis (13,(71)(72)(73)(74). TH3 is composed of an SH3 domain which has been suggested to either bind to yet undefined partners or intramolecularly to the Pro-rich TH2 domain.…”
Section: Structure/function Analysismentioning
confidence: 69%
“…Nevertheless, it has been shown that phagocytosis (7) and references therein) as well as part of axonal transport (8) and exocytosis (9) are actin-based movement. Endocytosis in yeast (10), vertebrates (11) and amoebae (12,13), polarized secretion in yeast (14), and fungi (15), vacuole inheritance in yeast (16), contractile vacuole function in amoebae (17), as well as blastoderm cellularization and cytoplasmic transport of particles in Drosophila (18,19), require specific myosin motors. Myosin V has now been shown to power the redistribution of melanosomes in mouse melanocytes (20,21), as well as in fish and Xenopus melanophores (22,23).…”
Section: Soldati Geissler and Schwarzmentioning
confidence: 99%
See 1 more Smart Citation